Explaining the Variation in Greenhouse Gas Emissions Between Households: Socioeconomic, Motivational, and Physical Factors. (26th September 2014) - Nässén, Jonas; Andersson, David; Larsson, Jörgen; Holmberg, John
Summary Consumption‐accounted greenhouse gas (GHG) emissions (GHGEs) vary considerably between households. Research originating from different traditions, including consumption research, urban planning, and environmental psychology, have studied different types of explanatory variables and provided different insights into this matter. This study integrates explanatory variables from different fields of research in the same empirical material, including socioeconomic variables (income, household size, sex, and age), motivational variables (proenvironmental attitudes and social norms), and physical variables (dwelling types and geographical distances). A survey was distributed to 2, 500 Swedish households with a response rate of 40%. GHGEs were estimated for transport, residential energy, food, and other consumption, using data from both the survey and registers, such as odometer readings of cars and electricity consumption from utility providers. The results point toward the importance of explanatory variables that have to do with circumstances rather than motivations for proenvironmental behaviors. Net income was found to be the most important variable to explain GHGEs, followed by the physical variables, dwelling type, and the geographical distance index. The results also indicate that social norms around GHG‐intensive activities, for example, transport, may have a larger impact on a subject's emission level than proenvironmental attitudes.